A Systematic Scoping Review of Essential Methodological Elements for Developing a Tool to Improve the Reporting of Consensus Studies in Classification, Diagnostic Criteria, and Guidelines Development - Medina YF; Mendieta CV; Prieto N; Acosta Felquer ML; Soriano ER (Journal of Multidisciplinary Healthcare)
Yimy F Medina,1,2 Cindy V Mendieta,1,3 Natalia Prieto,2 María Laura Acosta Felquer,4 Enrique R Soriano4 1Department of Clinical Epidemiology and Biostatistics, PhD Program in Clinical Epidemiology, Pontificia Universidad Javeriana, Bogotá, Colombia; 2Department of Internal Medicine, Rheumatology Unit, Faculty of Medicine, Universidad Nacional de Colombia, Bogotá, Colombia; 3Nutrition and Biochemistry Department, Faculty of Sciences, Pontificia Universidad Javeriana, Bogotá, Colombia; 4Internal Medicine Department, Rheumatology Section, Internal Medicine Service, Instituto Universitario Hospital Italiano, Buenos Aires, ArgentinaCorrespondence: Yimy F Medina, Email yimfmedinav@unal.edu.coIntroduction: A consensus is a general agreement among group members that is pivotal in gathering expert input for classification, diagnostic criteria, and guideline development. However, the absence of established methodological standards presents challenges in conducting and analyzing these studies.Objective: This scoping review explored the evidence on essential elements in consensus studies to create a list of candidate items for a standardized reporting tool. This tool is intended to improve the critical appraisal and methodological rigor of consensus studies.Methods: A systematic scoping review was conducted using predetermined criteria for study selecting studies and extracting data. A comprehensive literature search was performed without imposing date restrictions, covering multiple databases, including Medline, Embase, LILACS, SciELO, and up to March 2022. We included only English-language publications and excluded incomplete articles and conference reports. The risk of bias was assessed using the CASP checklist, and the study selection and data extraction were performed independently by two researchers in duplicate.Results: We identified 8360 references; 20 publications were included for data extraction. The majority (70%) used the Delphi method, and the remainder (30%) employed the modified Delphi method. Inconsistencies in reporting conflicts of interest and consensus timing were observed. Other methodologies, such as RAND/UCLA and Nominal Group Technique were excluded due to methodological limitations. Most studies exhibited a low risk of bias.Discussion: Our findings underscored the need for more standardization in definitions, methodology, and reporting within consensus studies. To address these gaps, we developed a checklist of key reporting items aimed at improving the planning, execution, and reporting consensus studies. Although the developed checklist requires validation, it offers a practical framework to enhance methodological transparency and reliability.Conclusion: Deficiencies and variability in consensus methodologies reporting underscore the need for a standardized approach. We propose the adoption of a checklist to strengthen the robustness of consensus studies, supporting advances in classification, diagnostic criteria, and guideline development.Keywords: consensus study, reporting guidelines, scoping review, methodology, completeness of reporting, excellent reporting